Being a Man: The Pursuit of Manliness in The Shepherd of Hermas - Young, Steve (Journal of early Christian studies, 1994)
The transformation of Hermas into a man functions as a plot device in The Shepherd of Hermas. In Visions 1-4, the female revealer exemplifies the traits of manliness extolled. Her metamorphosis corresponds to Hermas's own transformation toward manliness. Hermas's deficiency in manliness reflects the tensions over his leadership role as patron-paterfamilias, prophet and pastor within his house-church community and the perception that members of the community are becoming involved in business affairs in a way that undermines group boundaries and cohesion. The perceived crisis in the community corresponds to a crisis within the character of Hermas, resolved by Hermas's adopting the role of shepherd/pastor, signifying his renewed resolve to pursue his ministry within the community. This plot analysis supports the literary unity of the text. The text provides insight into the dynamics within an early house church. The role that the invocation of gender categories plays within the rhetorical construction of the Shepherd is highlighted.